UPAYA MENINGKATKAN REFORMASI BIROKRASI DI SEKRETARIAT JENDERAL DEWAN PERWAKILAN RAKYAT REPUBLIK INDONESIA - M. Dimyati Sudja (Jurnal Ilmu dan Budaya, 2019)
Bureaucratic reform needs to be implemented immediately because the bureaucracy has been regarded as something that is difficult, convoluted, unprofessional, high cost and full of practices of corruption, collusion and nepotism. The government began to feel uncomfortable with the status of civil servants who had arbitrary, corrupt, unprofessional, and high-cost titles. The government wants an increase in bureaucratic imagery in the eyes of the public, so that the government also wants immediate bureaucratic reform. With all the conditions and resistance they have, the authors are interested in conducting research qualitatively about efforts to improve bureaucratic reform at the Secretariat General of the House of Representatives of the Republic of Indonesia, using the Sedarmayanti concept (2009: 336), with the aim of knowing the factors that can improve bureaucratic reform at the Secretariat General of the House of Representatives of the Republic of Indonesia.